Impact of the SAC : CBZ ratio on polymorphic transformation and morphology of carbamazepine-saccharin co-crystals using fast cooling crystallization - Khairool Azizul, Mohammad; Wei, Michelle Ho Siaw; Engku Nuraishah Huda, Engku Zainudin; Syarifah, Abd Rahim (Springer Science and Business Media B.V., 2024)
Carbamazepine-saccharin (CBZ-SAC) co-crystal is one of the most studied co-crystals to date. It is proven to be polymorphic, consisting of Form I (plate-like shape) and Form II (needle-like shape), which is rarely reported by researchers. The present study aimed to study the effect of SAC:CBZ ratio on the polymorphic transformation and morphology of CBZ-SAC co-crystals using ice bath fast cooling crystallization. A series of CBZ-SAC co-crystals were produced from different SAC:CBZ mol ratios (1:1, 2:1, 3:1, 4:1, 5:1, 6:1) and were compared in terms of their crystal form and morphology under microscope. The polymorphic changes were also studied from the CBZ-SAC suspension during co-crystallization process. The polymorphs of CBZ-SAC co-crystals were identified using PXRD, DSC, ATR-FTIR. The results showed that at lower ratio (1:1, 2:1, 3:1), only plate-like shaped crystals (Form I) was present. For higher mol ratio (4:1, 5:1, 6:1), mixture of Form I and II of CBZ-SAC co-crystals were observed and further confirmed by DSC and ATR-FTIR. The nucleation process showed that Form II could convert to Form I when varying the SAC:CBZ ratio. Hence, it is proven that SAC:CBZ mol ratio can affect the polymorphic transformation and morphology of CBZ-SAC co-crystals. Nonetheless, other parameters should be used to further study the formation of CBZ-SAC co-crystals since pure CBZ-SAC Form II co-crystals were not obtained in this study.